Three-Dimensional Printing for Craniofacial Surgery: A Single Institution's 5-Year Experience. (July 2019) - Dumas, Blaike M.; Nava, Ana; Law, Huay-Zong; Smartt, James; Derderian, Christopher; Seaward, James R.; Kane, Alex A.; Hallac, Rami R.
Background: As 3-dimensional (3D) printers and models become more widely available and increasingly affordable, surgeons may consider investing in a printer for their own cleft or craniofacial center. To inform surgeons considering adoption of this evolving technology, this study describes one multi-surgeon center's 5-year experience using a 3D printer. Methods: This study included 3D models printed between October 2012 and October 2017. A 3D Systems ZPrinter 650 was used to create all models. Models were subclassified by type (craniofacial vs noncraniofacial) and diagnosis, and the cost of consumable materials was recorded. A survey was distributed to craniofacial team members who used the printed models. Likert scales and free texts were used for responses about lessons learned and the usefulness of the printer for different craniofacial indications. Results: A total of 106 models were printed at this institution during the 5-year time period. Printing times were 7.4 ± 1.9 hours for complete skulls and 6.0 ± 1.7 hours for maxillofacial prints. The average cost for a complete skull was about US60 in material cost alone. The 3D printer was most frequently used for complex craniosynostosis, hemifacial microsomia syndrome, and fibrous dysplasia cases. The surgeons found the printer to be most useful for planning complex facial orthognathic cases and least useful for routine single-suture synostosis. Conclusion: Three-dimensional printing was found to be helpful for all 4 craniofacial surgeons, who would all invest again in a 3D printer. For lower volume centers, commercially printed models may be a more cost-effective alternative.